On a Result of Hardy and Ramanujan - Charsooghi, Mohammad Avalin; Azizi, Yousof; Hassani, Mehdi; Mollazadeh-Beidokhti, Laleh (Sarajevo Journal of Mathematics, 2024)
In this paper, we introduce some explicit approximations for the summation _k≤ nΩ(k), where Ω(k) is the total number of prime factors of k. 2000 Mathematics Subject Classification. 05A10, 11A41, 26D15, 26D20